Narratives in corporate annual reports: the drivers and impacts of narrative's readability and tone. - Alrefaei, Hessa (Cranfield University, 2019)
Corporate annual reports have increased in size over time, not only to contain financial data but a plethora of narrative explanations concerning the firm’s current performance and their prospects. This thesis attempts to fill the gaps presented in the field of research of narrative disclosure in corporate reports by conducting three interconnected studies presented in a journal article manuscript form. The first paper provides an understanding of the drivers and consequences of narrative disclosure in corporate reports by conducting a systematic literature review of existing studies. The aim is to get a full understanding behind the intentions and consequences of narrative disclosures, to identify the gaps in research, and to provide recommendations for future research. The second paper focuses on the consequences of the readability of narratives, as an impression management technique in corporate annual reports. This study expands existing literature by not only analysing the reading difficulty of narratives but also touching on the use of ambiguous. It is found that readability (using both readability and ambiguity measures) are negatively associated with firm performance, indicating management’s use of impression management to obfuscate adverse performance, resulting in the reduction of performance persistence and firm value. The third paper focuses on earnings management as the driver of the tone of narratives. The study aims to find that relationship between earnings management (using accruals-based and real activities-based earnings management) and the tone of narratives, during two different strategic incentives that drive managers to manipulate earnings (meeting or beating prior year’s earnings and leverage increase). It is found that when managers practice income-increasing (decreasing) earnings management the tone is positive (negative). The findings signify that whether the intention is beneficial or harmful to investors, the tone of narratives is biased towards management’s intentions of earnings management practices.
Keywords: Narratives; corporate annual reports; impression management; tone; readability; systematic literature review